Images of the Merovingians and Carolingians - Bouchard, Constance Brittain (History compass, 2006)
For over a millennium, the perception of the role and achievements of the Merovingian and Carolingian dynasties, those that ruled the Franks from the mid-fifth to the late tenth century, was heavily shaped by writers working at the Carolingian court. These publicists sought to establish that the previous dynasty was made up of uncivilized incompetents, in strong contrast to their own ruling dynasty. Recently historians have begun examining this characterization not as a simple description of fact but rather as part of a conscious ninth-century plan to glorify the Carolingians. The Merovingians are now seen less as barbarians and more as Romanized Christians. Although historians do not denigrate the quite real Carolingian achievements, they are now analyzing the many models, from the kings of ancient Israel to the Caesars, to which the emperors were compared by their publicists.